Academic Networks and Disciplinary Trends: A Study of Mathematical Philosophy - Choudhary, Satyanarayan (NPRC Journal of Multidisciplinary Research, 2025)
Background: Mathematical philosophy has evolved as a significant interdisciplinary field linking formal logic, philosophy of science, and foundation mathematics. Despite its growing impact, detailed investigation of its research patterns, collaboration networks, and knowledge structures has been lacking. This piece bridges the gap through examination of the field’s evolution from 2015 to 2024, focusing on thematic shifts, intellectual drivers, and scholarly representation imbalances. Objective: This study attempts to examine the constitution and dynamics of research communities in philosophy of science, formal epistemology, and bordering disciplines through the cataloguing of leading researchers, clusters, and potential hierarchies or biases in terms of co-authorship and citation behavior. Methodology: A bibliometric analysis of 645 peer-reviewed articles (downloaded from lens.org) was conducted using VOSviewer and wordsift for visualizing the networks. Co-authorship analysis, citation mapping, keyword co-occurrence, and temporal trend analysis were methods used. Triangulation using qualitative content analysis ensured robustness. Findings: Dominance by strong Europeans existed in citation clusters by authors like Richard Dawid and Stephan Hartmann as hubs. Close-knit groups of co-authors found close-knit communities in Bayesian epistemology and formal logic, while sparse interdisciplinary connections were newly emerging. Keyword analysis suggested a shift to computational tendencies, though traditional subjects persisted. Gender and geographic disparities existed, with non-Western participation understated. Conclusion: The field boasts sound theoretical advancements but is marred by fragmentation and exclusionary gaps. Proposed recommendations include fostering cross-regional networks, addressing biases in citation, and exploring underserved subfields like applied mathematical ethics. Novelty: This contribution is new in presenting a comprehensive bibliometric analysis of mathematical philosophy and merging quantitative network analysis with strict qualitative noting. It offers a reflexive architecture for the assessment of intellectual and social processes in the field.